2020
DOI: 10.1210/clinem/dgaa448
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia and Islet Dysfunction Following Oral Glucose Tolerance Testing in Pancreatic-Insufficient Cystic Fibrosis

Abstract: CONTEXT Oral glucose tolerance test (OGTT)-related hypoglycemia is common in pancreatic insufficient cystic fibrosis (PI-CF), but its mechanistic underpinnings are yet to be established. OBJECTIVE To delineate the mechanism(s) underlying OGTT-related hypoglycemia. DESIGN AND SETTING We performed 180-minute OGTT with frequent blood sampling in adolescents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 38 publications
3
20
1
Order By: Relevance
“… 28 At the same time, glucagon release in response to low glucose is impaired in T1D and long lasting T2D increasing the risk of hypoglycemic episodes. 29 Along the same lines, Kilberg et al 21 showed that reduced glucagon secretion hours after a meal can lead to hypoglycemic events in CF patients diagnosed with pancreatic insufficiency. The dysregulation of glucagon secretion, with impaired high secretion in the early post-prandial phase 20 , 24 followed by a failed counter-regulatory response in the later phase 20 , 30 is not well understood.…”
Section: Biochemical and Histopathological Features Of Cfrdmentioning
confidence: 93%
See 2 more Smart Citations
“… 28 At the same time, glucagon release in response to low glucose is impaired in T1D and long lasting T2D increasing the risk of hypoglycemic episodes. 29 Along the same lines, Kilberg et al 21 showed that reduced glucagon secretion hours after a meal can lead to hypoglycemic events in CF patients diagnosed with pancreatic insufficiency. The dysregulation of glucagon secretion, with impaired high secretion in the early post-prandial phase 20 , 24 followed by a failed counter-regulatory response in the later phase 20 , 30 is not well understood.…”
Section: Biochemical and Histopathological Features Of Cfrdmentioning
confidence: 93%
“… 8 , 17 , 18 Insulin levels are lower in the first phase during an oral glucose tolerance test (OGTT) in CF and CFRD patients. 18 21 Also, there is an elevated secretion of proinsulin in both CFRD patients and CF patients with impaired glucose tolerance (IGT). 22 , 23 Failure to supress initial glucagon secretion following an OGTT correlates with decreased glucose tolerance among CF patients.…”
Section: Biochemical and Histopathological Features Of Cfrdmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoglycemia rates are higher during extended (3 or 4 hr) compared to standard (2 hr) OGTT. Postprandial hypoglycemia in CF patients has been reported as 6–15% on 2-hr OGTT [17] , 45–79% on 3-hr OGTT [17] , [20] , [21] , and 26% on mixed meal tolerance test (MMTT) [22] . In a study of youth with CF (mean age ∼ 14 years), Chan et al reported that rates of hypoglycemia on CGM, defined as time < 70 mg/dL and < 60 mg/dL, were not significantly different in subjects with CF (stratified according to glucose tolerance) compared to healthy controls [23] .…”
Section: Spontaneous Hypoglycemia In Cfmentioning
confidence: 99%
“…Some studies believed that β cell dysfunction started even before the impaired glucose tolerance [3,4] . It has been proved that in ammation in islet of T2DM patient is due to immune cell in ltration [5] , amyloid deposition [6] , cell death [7] and brosis [8,9] . Tumor necrosis factor α (TNF-α) and interleukin 6 (IL-6) as proin ammatory factors secreted by M1 macrophage [10] could impair insulin secretion through degrading insulin receptor substrate [11] .…”
Section: Introductionmentioning
confidence: 99%